2023
DOI: 10.1007/s12192-023-01363-8
|View full text |Cite
|
Sign up to set email alerts
|

Melissa officinalis extract suppresses endoplasmic reticulum stress-induced apoptosis in the brain of hypothyroidism-induced rats exposed to γ-radiation

Abstract: The purpose of this study was to demonstrate the neuroprotective effect of Melissa officinalis extract (MEE) against brain damage associated with hypothyroidism induced by propylthiouracil (PTU) and/or γ-radiation (IR) in rats. Hypothyroidism induction and/or exposure to IR resulted in a significant decrease in the serum levels of T3 and T4 associated with increased levels of lipid peroxidation end product, malondialdehyde (MDA), and nitrites (NO) in the brain tissue homogenate. Also, hypothyroidism and /or ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 57 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…These results support the favorable bioavailability and effectiveness of Relissa™ for its neuroprotective activity against oxidative stress damage. Moreover, the antioxidant effect of MO extracts evaluated in the present study is in agreement with previously reported studies ( Dastmalchi et al, 2008 ; López et al, 2009 ; Özkol et al, 2011 ; Lin et al, 2012 ; Martins et al, 2012 ; Ghazizadeh et al, 2020 ; Abd Allah et al, 2022 ; Abo-Zaid et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results support the favorable bioavailability and effectiveness of Relissa™ for its neuroprotective activity against oxidative stress damage. Moreover, the antioxidant effect of MO extracts evaluated in the present study is in agreement with previously reported studies ( Dastmalchi et al, 2008 ; López et al, 2009 ; Özkol et al, 2011 ; Lin et al, 2012 ; Martins et al, 2012 ; Ghazizadeh et al, 2020 ; Abd Allah et al, 2022 ; Abo-Zaid et al, 2023 ).…”
Section: Discussionsupporting
confidence: 93%
“…Extensive preclinical and clinical studies have suggested a therapeutic effect of MO extract supplementation as an efficacious and safe therapy to alleviate emotional distress conditions such as low mood, anxiety, and stress and improve sleep disorders ( Kennedy et al, 2002 ; Akhondzadeh et al, 2003 ; Kennedy et al, 2003 ; Kennedy et al, 2004 ; Kennedy et al, 2006 ; López et al, 2009 ; Cases et al, 2011 ; Alijaniha et al, 2015 ; Arceusz et al, 2015 ; Soltanpour et al, 2019 ; Noguchi-Shinohara et al, 2020 ). Reported evidence suggest that the active chemical constituents of MO extract possess diverse psycho- and neuropharmacological properties, including antidepressant ( Awad et al, 2007 ; Awad et al, 2009 ; López et al, 2009 ; Sahin et al, 2016 ), antioxidative stress ( Özkol et al, 2011 ; Martins et al, 2012 ; Ghazizadeh et al, 2020 ; Abd Allah et al, 2022 ; Abo-Zaid et al, 2023 ), and anti-inflammatory effects ( Baldwin et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Kochman et al [ 53 ] reported that the oxidative damage of cellular membrane lipids in hyperthyroid was higher than in euthyroid individuals. Conversely, it was found that M. officinalis protected the endogenous antioxidant system and minimized lipid peroxidation owing to its antioxidant potential [ 54 , 55 ]. Furthermore, Ghazizadeh et al [ 9 ] and Draginic et al [ 56 ] attributed the powerful antioxidant effect of the MO Extract to the higher content of phenolic compounds rosmarinic acid (RA), caffeic acid, cinnamic acid, gallic acid, and ferulic acid) besides, different flavonoids (luteolin, quercetin and others).…”
Section: Discussionmentioning
confidence: 99%